Cefepime versus piperacillin-tazobactam for the treatment of Pseudomonas aeruginosa pneumonia - Raneem H Pallotta; Walaiporn Wangchinda; Samantha R Sallerson; Gregory E Eschenauer; Vincent D Marshall; Virginia M Pierce; Jason M Pogue; Samuel L Aitken (Clinical Infectious Diseases, 2026)
Abstract Background Both piperacillin-tazobactam and cefepime are widely used for the treatment of pneumonia caused by Pseudomonas aeruginosa. Despite this, no studies have directly compared these agents for this purpose. Methods We performed a single-center retrospective cohort study of patients with pneumonia caused by P. aeruginosa treated with piperacillin-tazobactam or cefepime. The co-primary outcomes were 30-day mortality and a 30-day desirability of outcome ranking (DOOR) incorporating clinical failure, resistance, acute kidney injury (AKI), and recurrence. Overlap-weighted (OW) analyses were used to account for confounding. Results A total of 204 patients (piperacillin-tazobactam, n = 117; cefepime, n = 87) were included. Baseline characteristics were comparable between groups after OW. All-cause mortality occurred more frequently in patients who received piperacillin-tazobactam (23.1%) compared with those receiving cefepime (11.5%; p = 0.04, OW odds ratio 2.38, 95% CI 1.05–5.42). Conversely, no significant difference in the DOOR endpoint associated with receipt of piperacillin-tazobactam (46%, 95% CI 39% – 53%) was demonstrated. Rates of resistance development (12.0% vs 5.7%, p = 0.15; OW subhazard ratio 2.25, 95% CI 0.79–6.43), and clinical success (65% vs 70%; OW odds ratio 0.81, 95% CI 0.43–1.51) were similar amongst patients receiving piperacillin-tazobactam and cefepime, respectively. AKI incidence on study drug was likewise similar (7.0% vs 7.2%). Conclusion In this comparative study of cefepime and piperacillin-tazobactam for P. aeruginosa pneumonia, increased risk of mortality was seen with piperacillin-tazobactam. No differences were seen in other key outcomes, although sample size limits interpretation. This finding warrants further investigation in larger studies.